2007
DOI: 10.1080/02652030701329629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electron beam irradiation on deoxynivalenol levels in distillers dried grain and solubles and in production intermediates

Abstract: Wheat contaminated with deoxynivalenol (DON), and distillers dried grain and solubles (DDGS) obtained after ethanol production from the contaminated wheat, were irradiated to doses ranging from 2.0 to 55.8 kGy using an electron accelerator. Samples of wet distillers grain, distillers solubles and stillage obtained during production of DDGS were also irradiated. All samples were analysed for Fusarium trichothecene mycotoxins by a method involving use of gas chromatography-mass spectrometry (GC-MS). The three pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
0
16
0
3
Order By: Relevance
“…In the dry condition, both mycotoxins were stable to irradiation at 50 kGy. Using electron bean irradiation, Stepanik and others () also demonstrated a dose‐dependent reduction of DON contents in wet distiller grains used as feed supplement. Reductions reached 47.5% to 75.5% at the highest doses (about 50 kGy).…”
Section: Irradiation To Control Mold Growth and Mycotoxinsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the dry condition, both mycotoxins were stable to irradiation at 50 kGy. Using electron bean irradiation, Stepanik and others () also demonstrated a dose‐dependent reduction of DON contents in wet distiller grains used as feed supplement. Reductions reached 47.5% to 75.5% at the highest doses (about 50 kGy).…”
Section: Irradiation To Control Mold Growth and Mycotoxinsmentioning
confidence: 95%
“…The hydroxyl radicals remove hydrogen atoms from sugar and from the 4 bases of DNA strands (Lado and Yousef ). The other free radicals will also attack and break down organic molecules (Stepanik and others ). Potentially lethal DNA lesions are randomly scattered throughout the cell population during ionizing.…”
Section: The Food Irradiation Technologymentioning
confidence: 99%
“…At the irradiation dose of 50 kGy, the degradation rates of ZEN and OTA in corn kernel were 71.1% and 67.9%, respectively. Stepanik et al [34] found that the reduction of deoxynivalenol level in wet distillery grain, distiller’s solubles, and stillage exhibits a dose-dependent increase. Aziz et al [35] reported that gamma irradiation is effective against AFB 1 , ZEN, and OTA in food and agricultural products; at 20 kGy, AFB 1 and ZEN are completely disrupted and OTA content in samples is reduced by 72%–76%.…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity of transformation products had been lowered after heat treatment, but there was no phenomenon about the degradation of T-2 toxin [8]. Similarly, the obvious reduction of T-2 toxin amount in grains did not appear after treatment of γ-ray and electron beam [11]. The toxicity of T-2 toxin could be lowered by treatment of NaClO solution in NaOH, but it could result in the Chloride residue [12,13].…”
Section: Introductionmentioning
confidence: 99%